2006
DOI: 10.4103/0250-474x.25716
|View full text |Cite
|
Sign up to set email alerts
|

Effect of permeation enhancers on the release and permeation kinetics of Lincomycin hydrochloride gel formulations through mouse skin

Abstract: Lincomycin hydrochloride is a systemic antibiotic, which is active against most common gram positive bacteria. It has proved to be excellent for infectious diseases like acne, anthrax, pneumonia, and also for the treatment of furunculosis, carbuncles, impetigo, burns and wounds, carrying to gram positive bacteria. Gels were prepared using carbopol 940 as gelling agent, and isopropyl myristate and dimethyl sulfoxide as permeation enhancer. The formulations were evaluated for drug content, viscosity, pH, extruda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Dimethylsulfoxide and propylene glycol are reported to be the two best permeation enhancers (Panigrahi et al, 2006). Since DMSO reported to causes skin erosion we have used propylene glycol as permeation enhancer in the preparation of the gel formulation (Walker, Smith, 1996).…”
Section: Formulation and Evaluation Of Topical Herbal Gelmentioning
confidence: 99%
“…Dimethylsulfoxide and propylene glycol are reported to be the two best permeation enhancers (Panigrahi et al, 2006). Since DMSO reported to causes skin erosion we have used propylene glycol as permeation enhancer in the preparation of the gel formulation (Walker, Smith, 1996).…”
Section: Formulation and Evaluation Of Topical Herbal Gelmentioning
confidence: 99%
“…Rollback was prevented using clamp. The cap was removed and gel extruded until the pressure was degenerated (Panigrahi et al 2006;Srisombat et al 2005;Dave et al 2010;Hathout et al 2007). …”
Section: Extrudabilitymentioning
confidence: 99%
“…The in vitro drug release was carried out in triplicate for each preparation and expressed as Mean ± SD., and then the cumulative drug release (%CDR) was calculated and a plot of time versus %CDR was constructed and shown graphically. In vitro skin permeation studies were conducted for all liposome formulations and reported (Panigrahi et al 2006;Sezer et al 2004;Agarwal et al 2014).…”
Section: In Vitro Drug Releasementioning
confidence: 99%
“…Based on the high drug solubility, which was important to achieve, benzyl alcohol, oleic acid, and lemon oil were selected for preparation of the CTM microemulsions (24). Although the drug had a relative low solubility in IPM compared to other oils, it was also selected for the preparation of microemulsions due to its well-known permeation-enhancing property (25) and biocompatibility (26).…”
Section: Determination Of Saturation Solubility Of Ctm In Different Oilsmentioning
confidence: 99%